Iodine-mediated one-pot intramolecular decarboxylation domino reaction for accessing functionalised 2-(1,3,4-oxadiazol-2-yl)anilines with carbonic anhydrase inhibitory action - Srinivas Angapelly; P. V. Sri Ramya; Rohini Sodhi; Andrea Angeli; Krishnan Rangan; Narayana Nagesh; Claudiu T. Supuran; Mohammed Arifuddin (Journal of Enzyme Inhibition and Medicinal Chemistry, 2018)
A practical and transition metal-free one-pot domino synthesis of diversified (1,3,4-oxadiazol-2-yl)anilines has been developed employing isatins and hydrazides as the starting materials, in the presence of molecular iodine. The prominent feature of this domino process involves consecutive condensation, hydrolytic ring cleavage, and an intramolecular decarboxylation, in a one-pot process that leads to the oxidative formation of a C–O bond. Fluorescence properties of some of the representative molecules obtained in this way were studied. The synthesised 2-(1,3,4-oxadiazolo-2-yl)aniline-benzene sulphonamides (8a–o) were screened for their carbonic anhydrase (CA, EC 4.2.1.1) inhibitory activity. Most of the compounds exhibited low micromolar to nanomolar activity against human (h) isoforms hCA I, hCA II, hCA IV, and XII, with some compounds displaying selective CA inhibitory activity towards hCA II with KIs of 6.4–17.6 nM.